The prognostic value of MLL-AF9 detection in patients with t(9;11)(p22;q23)-positive acute myeloid leukemia - C Scholl; RF Schlenk; K Eiwen; H Dohner; S Frohling; K Dohner; AML Study Group (Haematologica, 2005)
BACKGROUND AND OBJECTIVES. Translocation (9;11) is the most common t(11q23) in acute myeloid leukemia (AML). A considerable number of patients with this cytogenetic abnormality relapse and die of their disease. We evaluated the clinical significance of minimal residual disease (MRD) monitoring in t(9;11)(p22;q23)-positive AML patients using real-time quantitative reverse transcriptase polymerase chain reaction (RQ-PCR) analysis. DESIGN AND METHODS. We identified 34 newly diagnosed patients with t(9;11)(p22;q23)-positive AML treated within three multicenter trials of the AML Study Group. MRD could be investigated by RQ-PCR in 19 patients during and after therapy. Because of the relatively low sensitivity of the RQ-PCR (10(-3) to 10(-4) at the cellular level), samples from RQ-PCR-negative patients were also analyzed by nested polymerase chain reaction (nPCR; sensitivity 10-4 to 10-5 at the cellular level). RESULTS. RQ-PCR monitoring revealed two groups of patients: group 1 (n=11) had negative RQ-PCR in all samples collected in hematologic complete remission whereas group 2 (n=8) had at least one positive RQ-PCR in samples collected in complete remission during therapy. Group 1 had a significantly lower cumulative incidence of relapse (p=0.004) and better overall survival (p=0.003) compared to group 2. nPCR did not add information to that gained from RQ-PCR. Molecular relapse was detected in two patients by RQ-PCR four and six weeks, respectively before hematologic relapse occurred. Quantitative MLL-AF9 levels at diagnosis or during and after therapy had no prognostic impact. INTERPRETATION AND CONCLUSIONS. Early achievement of sustained RQ-PCR negativity appears to be a prerequisite for long-term hematologic complete remission in t(9;11)-positive AML. Furthermore, RQ-PCR might be useful for early detection of relapse. Additional patients need to be studied to corroborate these findings.